Parosteal osteosarcoma: a diagnostic dilemma on non-healing following tooth extractions: a case report - Rahma Y. Damanhuri; Prihartiningsih Prihartiningsih; Poerwati S. Rahajoe (Journal of Dentomaxillofacial Science, 2018)
Objective: This paper reports a case of mandibular ramus parosteal osteosarcoma, discussing diagnostic problems and reviewing treatment variations. Methods: A 37 year old male patient was referred by a private hospital with a history of abscesses treatment and removal of his right lower molar 1.5 years ago. The wound in his tooth socket was not healed. Swelling with abscesses recurred and was diagnosed as osteomyelitis. The Orthopantomogram (OPG) result showed a description of osteomyelitis, and the Multi Slice Computed Tomography (MSCT) 3D confirmed the suspected osteosarcoma. Histopathologic results indicated parosteal osteosarcoma.Â Result: Hemimandibulectomy and chemotherapy were performed with good results.Conclusion: This parosteal osteosarcoma was difficult to diagnosis quickly because the initial image resembled osteomyelitis but it was low grade and rare; therefore, meticulous and accurate diagnosis was deemed necessary. Chemotherapy-combined surgery was thereby performed for treating this parosteal osteosarcoma.